Metformin Suppressed CXCL8 Expression and Cell Migration in HEK293/TLR4 Cell Line - Zhihui Xiao; Wenjun Wu; Vladimir Poltoratsky (Mediators of Inflammation)
Chronic inflammation is associated with cancer. CXCL8 promotes tumor microenvironment construction through recruiting leukocytes and endothelial progenitor cells that are involved in angiogenesis. It also enhances tumor cell proliferation and migration. Metformin, type II diabetes medication, demonstrates anticancer properties via suppressing inflammation, tumor cell proliferation, angiogenesis, and metastasis. This study intended to address the role of metformin in regulation of CXCL8 expression and cell proliferation and migration. Our data indicated that metformin suppressed LPS-induced CXCL8 expression in a dose-dependent manner through inhibiting NF-κB, but not AP-1 and C/EBP, activities under the conditions we used. This inhibitory effect of metformin is achieved through dampening LPS-induced NF-κB nuclear translocation. Cell migration was inhibited by metformin under high dose (10 mM), but not cell proliferation.